GPR55 is expressed in glutamate neurons and functionally modulates drug taking and seeking in rats and mice - Yi He; Hui Shen; Guo-Hua Bi; Hai-Ying Zhang; Omar Soler-Cedeño; Hannah Alton; Yihong Yang; Zheng-Xiong Xi (Translational Psychiatry, 2024)
Abstract G protein-coupled receptor 55 (GPR55) has been thought to be a putative cannabinoid receptor. However, little is known about its functional role in cannabinoid action and substance use disorders. Here we report that GPR55 is predominantly found in glutamate neurons in the brain, and its activation reduces self-administration of cocaine and nicotine in rats and mice. Using RNAscope in situ hybridization, GPR55 mRNA was identified in cortical vesicular glutamate transporter 1 (VgluT1)-positive and subcortical VgluT2-positive glutamate neurons, with no detection in midbrain dopamine (DA) neurons. Immunohistochemistry detected a GPR55-like signal in both wildtype and GPR55-knockout mice, suggesting non-specific staining. However, analysis using a fluorescent CB1/GPR55 ligand (T1117) in CB1-knockout mice confirmed GPR55 binding in glutamate neurons, not in midbrain DA neurons. Systemic administration of the GPR55 agonist O-1602 didnt impact ∆9-THC-induced analgesia, hypothermia and catalepsy, but significantly mitigated cocaine-enhanced brain-stimulation reward caused by optogenetic activation of midbrain DA neurons. O-1602 alone failed to alter extracellar DA, but elevated extracellular glutamate, in the nucleus accumbens. In addition, O-1602 also demonstrated inhibitory effects on cocaine or nicotine self-administration under low fixed-ratio and/or progressive-ratio reinforcement schedules in rats and wildtype mice, with no such effects observed in GPR55-knockout mice. Together, these findings suggest that GPR55 activation may functionally modulate drug-taking and drug-seeking behavior possibly via a glutamate-dependent mechanism, and therefore, GPR55 deserves further study as a new therapeutic target for treating substance use disorders.